Phantom limb perception interferes with motor imagery after unilateral upper-limb amputation - Lyu, Yuanyuan; Flor, Herta (Scientific reports, 2016)
A potential contributor to impaired motor imagery in amputees is an alteration of the body schema as a result of the presence of a phantom limb. However, the nature of the relationship between motor imagery and phantom experiences remains unknown. In this study, the influence of phantom limb perception on motor imagery was investigated using a hand mental rotation task by means of behavioral and electrophysiological measures. Compared with healthy controls, significantly prolonged response time for both the intact and missing hand were observed specifically in amputees who perceived a phantom limb during the task but not in amputees without phantom limb perception. Event-related desynchronization of EEG in the beta band (beta-ERD) in central and parietal areas showed an angular disparity specifically in amputees with phantom limb perception, with its source localized in the right inferior parietal lobule. The response time as well as the beta-ERD values were significantly positively correlated with phantom vividness. Our results suggest that phantom limb perception during the task is an important interferential factor for motor imagery after amputation and the interference might be related to a change of the body representation resulting from an unnatural posture of the phantom limb.
Gesehen am 04.02.2019